2016
DOI: 10.1177/0146167216647360
|View full text |Cite
|
Sign up to set email alerts
|

Directionality of Person–Situation Transactions

Abstract: To elucidate temporal sequences among and between person and situation variables, this work examines cross-measurement spillovers between situation experiences S (on the Situational Eight DIAMONDS characteristics [Duty, Intellect, Adversity, Mating, pOsitivity, Negativity, Deception, Sociality]) and personality states P (on the Big Six HEXACO dimensions [Honesty/Humility, Emotionality, eXtraversion, Agreeableness, Conscientiousness, Openness to Experience]) in experience sampling data. Multi-level modeling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 72 publications
2
49
0
Order By: Relevance
“…The authors concluded that "[u]ltimately, both personality traits and experienced situation characteristics 3 The data from Study 1 were initially published in Sherman et al (2015). Since then, they were also used in Rauthmann et al (2016), Jones et al, (2017), and Rauthmann et al (2019). None of these articles has addressed the same questions that are addressed in the current study.…”
Section: Studymentioning
confidence: 96%
See 2 more Smart Citations
“…The authors concluded that "[u]ltimately, both personality traits and experienced situation characteristics 3 The data from Study 1 were initially published in Sherman et al (2015). Since then, they were also used in Rauthmann et al (2016), Jones et al, (2017), and Rauthmann et al (2019). None of these articles has addressed the same questions that are addressed in the current study.…”
Section: Studymentioning
confidence: 96%
“…Situation characteristics that were assessed with standardized and validated measures allowed theoretically meaningful predictions of behavior in several instances (Brown et al, 2015;Gerpott et al, 2017;Parrigon et al, 2017;Rauthmann et al, 2014;Ziegler et al, 2019). Further, several situation dimensions have been explicitly linked to behavioral manifestations of personality traits (de Vries, Tybur, Pollet, & van Vugt, 2016;Parrigon et al, 2017;Rauthmann, Jones, & Sherman, 2016;Sherman et al, 2015).…”
Section: Situational Taxonomies and Measures Rauthmann And Colleaguesmentioning
confidence: 99%
See 1 more Smart Citation
“…While experimental studies have the advantage of controlling the independent variable, thus enabling the researcher to draw stronger conclusions about causation (see West & Thoemmes, 2010, for a review), cross-lagged analyses in experience sampling studies provide a more ecologically valid examination of how personality and well-being states may influence one another within individuals in daily life and provide insight into directions of influence (Rauthmann, Jones, & Sherman, 2016).…”
Section: Directions Of Association Between Personality and Well-beimentioning
confidence: 99%
“…Cross‐lagged analyses allow for the examination of the extent to which (a) personality states in one moment predict change in well‐being at the next measurement occasion (Figure , path c ) and whether (b) well‐being in one moment predicts change in personality states at the next measurement occasion (Figure , path d ). While experimental studies have the advantage of controlling the independent variable, thus enabling the researcher to draw stronger conclusions about causation 9see West & Thoemmes, , for a review), cross‐lagged analyses in experience sampling studies provide a more ecologically valid examination of how personality and well‐being states may influence one another within individuals in daily life and provide insight into directions of influence (Rauthmann, Jones, & Sherman, ).…”
Section: Introductionmentioning
confidence: 99%